The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.2190/de.40.3.e
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes about Addiction: A National Study of Addiction Educators

Abstract: The following study, funded by the National Institute of Drug Abuse (NIDA), utilized the Addiction Belief Inventory (ABI; Luke, Ribisl, Walton, & Davidson, 2002) to examine addiction attitudes in a national sample of U.S. college/university faculty teaching addiction-specific courses (n=215). Results suggest that addiction educators view substance abuse as a coping mechanism rather than a moral failure, and are ambivalent about calling substance abuse or addiction a disease. Most do not support individual effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The ‘brain disease model’ of addiction is ostensibly a technical, apolitical framing of the concept, which mobilizes science and evidence rather than ideology. Yet research on the reception of the brain disease model by neuroscientists and clinicians (Bell et al, 2014), practitioners in drug treatment services (Broadus et al, 2010), and lay publics (Meurk et al, 2013), indicates scepticism about it (also see Martin, 2010, concerning mental illness). This scepticism comes from fears that the disease model will replace multifactorial approaches to alcohol and other drug use, and side-line human agency and choice.…”
Section: Debating Addiction the Brain And Materialitymentioning
confidence: 99%
“…The ‘brain disease model’ of addiction is ostensibly a technical, apolitical framing of the concept, which mobilizes science and evidence rather than ideology. Yet research on the reception of the brain disease model by neuroscientists and clinicians (Bell et al, 2014), practitioners in drug treatment services (Broadus et al, 2010), and lay publics (Meurk et al, 2013), indicates scepticism about it (also see Martin, 2010, concerning mental illness). This scepticism comes from fears that the disease model will replace multifactorial approaches to alcohol and other drug use, and side-line human agency and choice.…”
Section: Debating Addiction the Brain And Materialitymentioning
confidence: 99%
“…However, there is not universal support for the idea that addiction is a disease. A national survey of higher education faculty who teach courses about addiction found very low support (less than 20%) for the notion that addiction is a disease (Broadus, Hartje, Roget, Cahoon, & Clinkinbeard, 2010). Other research has shown that while some may view addiction as a disease, it is not as high as the proportion that views mental illness as a disease (Alcoholism and Drug Abuse Weekly, 2010; Corrigan, Kuwabara, & O’Shaughnessy, 2009).…”
Section: Research On Drug Policy Attitudesmentioning
confidence: 99%
“…There was also an association between attaining a college degree and views about addiction as a disease. There were no significant differences between women and men in their attitudes toward addiction as a disease (Broadus et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 92%
“…In the United States, Broadus et al (2010) found that more than half of the respondents (57.5%) were in the neutral range, less than 20 percent of respondents believed that addiction is a disease, and most respondents (93.3%) believed that people living with addictions are responsible for their recovery. There was also an association between attaining a college degree and views about addiction as a disease.…”
Section: Literature Reviewmentioning
confidence: 99%